2022
DOI: 10.3390/coatings12040530
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Analytical Investigation of Roman Frescoes from Rapoltu Mare (Romania)

Abstract: (1) Background: Due to the precarious situation of many monuments or archeological sites, analytical investigations are necessary to obtain information about the used materials, as well as to identify the most appropriate solutions for their conservation/restoration. This paper addresses the characterization of mural painting fragments collected during the excavation in 2018 in Rapoltu Mare (La vie), Deva. (2) Methods: Specific analytical techniques were used, as follows: X-ray diffractometry (XRD), wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…In this case, the presence of iron compounds was interpreted as intentionally added in little portion to calcium carbonate to achieve a slightly pale pink color. These results, however, are consistent with other studies of white pigments used in ancient Roman wall paintings [12].…”
Section: Whitesupporting
confidence: 93%
“…In this case, the presence of iron compounds was interpreted as intentionally added in little portion to calcium carbonate to achieve a slightly pale pink color. These results, however, are consistent with other studies of white pigments used in ancient Roman wall paintings [12].…”
Section: Whitesupporting
confidence: 93%
“…Except the visible surface cracks, thermographic inspection put into evidence further cracking, difficult to be detected through visual testing (Figure 3). The physicochemical analysis, absolutely necessary in such experiments [17], was performed in this paper using WDXRF, XRD and FTIR. WDXRF allowed to see the elemental composition of mortar samples taken from the bricks existing in the fortress, It can be found that, on the same stone component, there can be differences of about 10-15 • C, which give the organisms associated with these surfaces' adequate ecological adaptations and allow them to survive in this type of microhabitat.…”
Section: Resultsmentioning
confidence: 99%
“…Except the visible surface cracks, thermographic inspection put into evidence further cracking, difficult to be detected through visual testing (Figure 3). The physicochemical analysis, absolutely necessary in such experiments [17], was performed in this paper using WDXRF, XRD and FTIR. WDXRF allowed to see the elemental composition of mortar samples taken from the bricks existing in the fortress, The physicochemical analysis, absolutely necessary in such experiments [17], was performed in this paper using WDXRF, XRD and FTIR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations